Position Of Covernote In Fulfilling The Requirements Of A Credit Agreement In Banking - Cahyadi, I Kadek Hery (Inspiring Law Journal, 2024)
The role and function of Notary-PPAT is very important in assisting the government, especially the banking sector, or other parties who need the presence of a Notary to be able to provide certainty, order, and legal protection in legal acts that are stated in authentic deeds. In addition to authentic deeds and private letters made by Notaries, there is one type of letter that seems to be a Notary's legal product that is often requested by banks to be made and issued in order to guarantee a legal act of the interested parties, namely a statement letter used as a temporary guarantee called a covernote. The position of the covernote in fulfilling the requirements of the credit agreement in banking becomes a complement if there is a process that has not been completed on the credit guarantee, the creditor (bank) asks the Notary-PPAT to make and issue a covernote, although the covernote is not part of the process for making a deed of encumbrance of rights. The covernote is proof of the binding of the guarantee and/or temporary hold for the bank in disbursing the credit. At the request of the bank, the Notary-PPAT makes and issues a covernote because the administration of the binding of the guarantee at the land office by the Notary-PPAT has not been completed